Computational Simulations; Abundant Optical Wave Solutions Atangana Conformable Fractional Nonlinear Schrodinger Equation - Khater, Mostafa M. A.; İnç, Mustafa; Attia, Raghda A. M.; Lu, Dianchen (Wiley, 2022)
This research paper explores the Atangana conformable nonlinear fractional Schrodinger equation's optical soliton wave solutions through three recently introduced computational schemes. The simplest expanded equation, the generalized Kudryashov method, and the sech-tanh expansion approaches are used for describing the structure of optical solitons by nonlinear optical fibers with the modern fractional operator. Several formulas such as hyperbolic, trigonometric, logical, dim, light, moon-bright hybrid, singular, combined singular, and regular wave solutions have been created. The employed methods are effective and worthy of being tested. The features of the Hamiltonian process were used to analyze the stability properties of the solutions obtained.
Keywords: Perturbation; Solitons; Model